Associations between physical activity and cardiorespiratory fitness and adverse outcomes in patients with atrial fibrillation: a prospective cohort study - Chen, Yanwen; Wang, Yutong; Song, Xinyang; Xu, Tao; Wang, Fang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCardiorespiratory fitness (CRF) and physical activity (PA) are crucial for health and are gaining prominence in sports cardiology and rehabilitation medicine. This research study analyzes the impact of CRF and PA on the cardiovascular prognosis of patients with atrial fibrillation (AF), offering insights to optimize exercise interventions and enhance the scientific use of exercise in health.MethodsCox regression models were used to assess the associations between CRF, PA, and endpoint events, including heart failure, stroke, myocardial infarction, and all-cause mortality. PA was categorized into four intensity levels, while CRF was quantified using three metrics: maximal oxygen uptake, (VO2max) resting heart rate (RHR), and maximum heart rate. To further examine the dose–response relationship, restricted cubic spline models were employed to assess potential non-linear associations.ResultsIncreased total physical activity [hazard ratio (HR) = 0.978; 95% confidence interval (CI): 0.961–0.995, P = 0.011], moderate-to-vigorous PA (HR = 0.960; 95% CI: 0.929–0.992, P = 0.014), and moderate physical activity (MPA) (HR = 0.953; 95% CI: 0.918–0.990, P = 0.014) were significantly associated with a decreased risk of major adverse cardiovascular events, respectively. All levels of PA were significantly associated with a decreased risk of cardiovascular death with HRs ranging from 0.577 to 0.938 (P < 0.01). Higher RHR was significantly associated with an increased risk of adverse outcomes, but not with stroke (HR = 0.999, 95% CI: 0.991–1.007, P = 0.7854) or cardiovascular death (HR = 1.004, 95% CI: 0.996–1.013, P = 0.3504). In addition, higher VO2max was significantly associated with a lower risk of adverse outcomes, except for cardiovascular death (HR = 0.956, 95% CI: 0.888–1.030, P = 0.2376).ConclusionThis study shows that MPA significantly reduces cardiovascular risks in patients with AF, with all PA levels lowering mortality. Any PA level is beneficial, leading to immediate improvements, but excessive PA may yield diminishing returns or risks. Focusing solely on intensity or duration is insufficient; scientifically designed interventions, especially those boosting CRF (e.g., VO2max), have a greater effect on AF prognosis. Future programs should integrate scientifically grounded strategies to maximize benefits.